Luto e desigualdade social: uma leitura sócio-histórica sobre a morte e o luto a partir das experiências do território da Brasilândia no contexto da pandemia de Covid-19 - Ferreira, Camila Moraes (2021)
This research relies on the assumption that social inequality, as a structural dimension of Brazilian social relations and subjectivities, constitutes and defines death and grieving processes. Historically, the psychology field, however, has reproduced theoretical and practical perspectives which tend to naturalize death and universalize the grieves, distancing itself from the social base of these phenomena and concealing the unequal forms in which they occur in the country, based on the oppressions of class-race-gender. Starting from a criticism of this understanding, on the basis of the theoretical-methodological reference of the Socio-Historical Psychology, this study had as objective to build a social-historical reading of the death and grief processes in its relation with the social inequality, analysing them in the Brasilândia territory during the Covid-19 Pandemic. Six community leaderships were interviewed in Brasilândia, a peripheral territory located in São Paulo's northern area. The research data were discussed on the basis of the Nuclei of Meaning methodology, coming up to the main meanings built by the participants in the pandemic context, facing death and grieving in the territory. As outcome, two main nuclei were elaborated: the Nuclei 1, in which we discussed the meanings regarding the pandemic repercussions on the territory, characterizing the context and the research background; the Nuclei 2, in which we present the meanings regarding the deaths and grieves. The pandemic has appeared in these meanings as an emblematic phenomenon that has increased and deepened the historical social inequality in the territory and brought impacts in the life conditions of the population. In the face of the emergency of these social demands and the absence of the public authorities, the collective organizations have gained centrality and have reassured themselves as even more urgent. Death was signified as a recurrent phenomenon, to which the population is exposed on a daily basis, even before the pandemic. The racial issue was central to these experiences; black and peripheral youth are the bigger victims of death by violence. Contradictorily, facing these wide open deaths, the grieving processes tend to be silenced and non-acknowledged. Thus, the grieving experience revealed itself attached to the struggles, in a dialectical relation, as a political act and gesture in direction to the commitment with life. Finally, it was reiterated the importance of a practice in Psychology that, denaturalizing the grieving processes, acknowledges them as ethical-political sufferings, phenomena defined by a social dimension. We point, lastly, to the necessity of building grieving care practices socially committed and articulated with the demands of the concrete life of each population